2018
DOI: 10.1002/adom.201800137
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Saturable and Excited‐State Absorption in Bulk ReS2

Abstract: The intensity‐scan (I‐scan) technique to study the polarization‐dependent, nonlinear processes in exfoliated bulk ReS2 is utilized. The polarization‐dependent reflection and transmission of ReS2, from which the absorption coefficients are extracted using the transfer matrix method, are measured. Absorption coefficients under high laser peak power show a transition from saturable absorption (SA) to reverse saturable absorption when rotating the laser polarization with respect to the b‐axis. It is found that SA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 67 publications
0
40
0
Order By: Relevance
“…Recent optical studies have revealed indirect band gap natures in atomically thinlayered materials with thicknesses ranging from seven down to single monolayers. In few-layered ReS 2 , very fast transient optical responses (< 1ps) due to the photogenerated carriers and ultrafast optical fields have been studied [12,39,40] . However, the transient dynamics of photogenerated electronhole pairs (excitons) and their whole relaxation processes have not been fully understood by comprehensive studies in the time scale range of subpicoseconds to subnanoseconds, despite the fact This article is protected by copyright.…”
Section: Introductionmentioning
confidence: 99%
“…Recent optical studies have revealed indirect band gap natures in atomically thinlayered materials with thicknesses ranging from seven down to single monolayers. In few-layered ReS 2 , very fast transient optical responses (< 1ps) due to the photogenerated carriers and ultrafast optical fields have been studied [12,39,40] . However, the transient dynamics of photogenerated electronhole pairs (excitons) and their whole relaxation processes have not been fully understood by comprehensive studies in the time scale range of subpicoseconds to subnanoseconds, despite the fact This article is protected by copyright.…”
Section: Introductionmentioning
confidence: 99%
“…ReS 2 is one of the group-VII transition metal dichalcogenides, which possesses anisotropic exciton absorption due to the reduced crystal symmetry [ 56 , 124 , 125 ]. Figure 3(e) shows the reflection contrast spectra of monolayer ReS 2 , where the dramatic shifts of the absorption peaks arise from the competition of two near-gap excitons (labeled as red and black arrows) [ 126 ].…”
Section: Anisotropic Materials and Optical Propertiesmentioning
confidence: 99%
“…Two-dimensional (2D) layered materials, such as graphene [1][2][3], transition metal chalcogenides (TMDCs) [4][5][6][7][8][9], and topological insulators (TIs) [10][11][12][13], have received tremendous research attention in optical, electronic, and optoelectronic applications, due to their outstanding physical and chemical properties [11,[14][15][16][17]. Most materials mentioned above are isotropic with polarization-independent optical and electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Differently, another group of materials with low lattice symmetry, such as black phosphorus (BP) [18][19][20], rhe-nium disulfide (ReS 2 ) [21,22], and gallium telluride (GaTe) [23], have recently attracted attention for their polarization-dependent thermal conductivity [24], optical absorption [14], and third harmonic generation (THG) [25]. As for anisotropic materials, there are mainly two typical types of in-plane atom structures [26]: the first one is ReS 2 -like TMDC, which consists of atoms distributed in disordered trigonal (1T) structure [14]; the other one is a material represented by black phosphorus (BP), such as four-six-enes [27], which shows a puckered honeycomb structure. In contrast to other hexagonal (2H) TMDCs, the origin of anisotropy in 1T structure of ReS 2 is caused by the additional d valence electron of the Re atoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation